PENGARUH PENGURANGAN IMPOR BERAS PAKISTAN TERHADAP PETANI BERAS INDONESIA - Fitri, Alissha; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Along with the increasing rice consumption of Indonesian people, the national rice production also increase. The rice production in Indonesia increases but the government remains to import the rice in order to fulfill the domestic rice demand. The rice import development of Indonesia tends to be fluctuative every year. The biggest rice import that enters into Indonesia comes from Vietnam and Thailand. Both countries are the countries that have the biggest rice production total in Asia. Hence, the high price from the both countries, so Indonesia chooses to import Pakistan’s rice where this country is the fourth rice production country with the low price. The method of data collecting is done by collecting secunder data, then analyzed in qualitative to obtain the draft about the main problem by using deductive method. The method of this research is the method of qualitative descriptive. The data is obtained through secunder data such as, book, journal, magazine, newspaper and website. From the research result, for fulfilling the own rice needs and making the local farmer prosperous so Indonesia increases the productivity and the increase of plantation index to be three times. This thing has goal to increase the national food security productivity by decreasing the rice import intencity. Keywords: Pakistan’s rice, import, Indonesia’s rice farmer